Web-based Collaborative Working Environment and Sustainable Furniture Design - Su, D.; Casamayor, J. (Cranfield University Press, 2009)
To meet the demand of online collaborative design, a Web-based Collaborative Working Environment (CWE) has been developed. An approach to enhance sustainable furniture design by utilizing the CWE is proposed. In this paper, the CWE framework is briefly presented, which consists of upperware, middleware and resource layers; then three key aspects of sustainable furniture design by utilizing the CWE are presented, including material and manufacturing processes selection, design for disassembly and damaged furniture return, followed by an example of damaged furniture return using the CWE to further illustrate the approach.
Organised by: Cranfield University
Keywords: Collaborative Working Environment; Web/Internet technology; Sustainable Design; Furniture Design